Comparison of the effects of AgNPs on the morphological and mechanical characteristics of cancerous cells. (6th January 2023) - Zhu, Jiajing; Tian, Yanling; Cao, Liang; Hu, Jing; Yan, Jin; Wang, Zuobin; Liu, Xianping
Abstract: Currently, silver nanoparticles (AgNPs) are the most produced nanoparticles in global market and have been widely utilized in the biomedical field. Here, we investigated the morphological and mechanical effects of AgNPs on cancerous cells of A549 cells and SMMC‐7721 cells with atomic force microscope (AFM). The influence of AgNPs on the morphological properties and mechanical properties of cancerous cells were characterized utilizing the force–volume (FV) mode and force spectroscopy (FS) mode of AFM measurement. We mainly focus on the comparison of the effects of AgNPs on the two types of cancerous cells based on the fitting results of calculating the Young's moduli utilizing the Sneddon model. The results showed that the morphology changed little, but the mechanical properties of height, roughness, adhesion force and Young's moduli of two cancerous cells varied significantly with the stimulation of different concentrations of AgNPs. This research has provided insights into the classification and characterization of the effects of the various concentrations of AgNPs on the cancerous cells in vitro by utilizing AFM methodologies for disease therapy. Lay description: Atomic force microscope (AFM) provides a direct method to measure the morphological and mechanical properties of cells in real time at the atomic scale with high force sensitivity and precise spatial resolution. In addition, the AFM‐based indentation method has unique advantages of small deformation and less damage to living cells. Currently, silver nanoparticles (AgNPs) are the most produced nanoparticles in global market and have been widely utilized in the biomedical field. Even though the AFM has been invented by Binnig, Gerber and Quate in 1985, the influence of AgNPs on cells with AFM‐based indentation method was still rarely investigated in recent years. In this research, we investigated the comparison of the effects of AgNPs on the two types of cancerous cells of A549 cells and SMMC‐7721 cells with emphasis on the morphological and mechanical changes by utilizing inverted optical microscopy, FIB, two types of AFM modes of force‐volume (FV) mode and force spectroscopy (FS) mode. The results showed that the morphology changed little, but the mechanical properties of height, roughness, adhesion force and Young's moduli of two cancerous cells varied significantly with the stimulation of different concentrations of AgNPs. This research has provided insights into the characterization of the effects of the various concentrations of AgNPs on the cancerous cells in vitro by utilizing AFM methodologies for disease therapy.